SWOT & QSPM as A Strategy to Increase Customer Loyalty of Ekawarsa Plus Partners at AJB Bumiputera 1912 Medan - Rahma Wulan Suci Nasution; Muhammad Syahbudi; Ahmad Muhaisin B. Syarbaini (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2023)
The cause of the decrease in the number of policies is due to a strategy to increase customer loyalty that is lacking in the company, where this strategy has a very big impact on increasing or decreasing the number of policies on the product chosen by each customer. Customer loyalty is a form of customer commitment to a product repeatedly and even permanently. Mitra Ekawarsa Personal Accident is a form of self-protection from risks that might occur. Qualitative research is obtained from primary data sources by conducting direct observations at companies, conducting interviews, secondary data is complementary data used as a basic reference for theory, obtained through jurnals, etc. The aim of this research is to find out how to increase loyalty to a Mitra Ekawarsa Plus Personal Accident product at the AJB Bumiputera 1912 Mean company using SWOT & QSPM analysis. The ST strategy in this research is making a strategy by applying the company's internal strengths so that it can avoid or minimize the consequences of several threats originating from foreign companies. The results of this stage show that increasing numbers of employees in the marketing department who are honest and responsible has the highest TAS score with a value of 4.905. Thus, increasing the number of employees in the marketing department who are honest and responsible is a recommended strategy that companies should implement in order to increase customer loyalty to the company.